MODEL PENGELOLAAN DAN PEMBERDAYAAN EKONOMI UMAT DI MASJID SALMAN ITB - NURSAADAH, SITI KOMALA; Mudzakir, Ahmad (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2022)
AbstractThe purpose of this study is to find out what the potential of the Salman ITB Mosque is, to find out how the economic management of the people at the Salman ITB Mosque is, and to know the process of empowering the economy of the people at the Salman ITB Mosque. The type of research used in this study is a qualitative descriptive method. Data collection in this study is by means of interviews and documentation. Interviews were conducted online using Google Meeting and met directly with the mosque management and economic management institutions at the Salman Mosque ITB. The results of this study are the potential of the Salman Mosque ITB, namely in terms of facilities and resources that are qualified and professional. Salman Mosque has facilities such as building rentals, kiosks, libraries, cooperatives, canteens, parking lots, and Charity Houses. For the economic management of the people or employees at the Salman Mosque, it is managed by the United Salman Cooperative. This cooperative was established with the aim of helping the welfare of members where members of this cooperative come from employees within Salman's own environment. The empowerment process carried out by the Salman Cooperative is Formation, Training, and Independence. AbstrakTujuan dari penelitian ini adalah untuk mengetahui apa saja potensi yang dimiliki oleh Masjid Salman ITB, mengetahui bagaimana pengelolaan ekonomi umat di Masjid Salman ITB, dan mengetahui proses pemberdayaan ekonomi umat di Masjid Salman ITB. Jenis penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Pengumpulan data dalam penelitian ini yaitu dengan cara wawancara dan dokumentasi. Wawancara dilakukan secara online menggunakan Google Meeting dan bertemu secara langsung dengan pihak pengurus masjid dan lembaga pengelolaan ekonomi di Masjid Salman ITB. Hasil dari penelitian ini adalah potensi yang dimiliki oleh Masjid Salman ITB yaitu dari segi fasilitas dan Sumber Daya yang dimiliki sudah berkualitas dan profesional. Masjid Salman mempunyai fasilitas seperti penyewaan gedung, kios, perpustakaan, koperasi, kantin, lahan parkir, dan Rumah Amal. Untuk pengelolaan ekonomi umat atau para karyawan di Masjid Salman dikelola oleh Koperasi Salman Bersatu. Koperasi ini didirikan dengan tujuan untuk membantu kesejahteraan anggota yang mana anggota Koperasi ini berasal dari karyawan yang ada dilingkungan Salman itu sendiri. Proses pemberdayaan yang dilakukan oleh Koperasi Salman yaitu Pembentukan, Pelatihan, dan Pemandirian.